Nonlinear analysis of buckling and postbuckling for axially compressed functionally graded cylindrical panels with the Poisson’s ratio varying smoothly along the thickness - Dung, Dao Van; Hoa, Le Kha (Vietnam Journal of Mechanics, 2012)
In this paper an approximate analytical solution to analyze the nonlinear buckling and postbuckling behavior of imperfect functionally graded panels with the Poisson’s ratio also varying smoothly along the thickness is investigated. Based on the classical shell theory and von Karman’s assumption of kinematic nonlinearity and applying Galerkin procedure, the equations for finding critical loads and load-deflection curves of cylindrical panel subjected to axial compressive load with two types boundary conditions, are given. Especially, the stiffness coefficients are analyzed in explicit form. Numerical results show various effects of the inhomogeneous parameter, dimensional parameter, boundary conditions on nonlinear stability of panel. An accuracy of present theoretical results is verified by the previous well-known results.